THE EFFECT OF THE SOUTH AFRICAN MEDIA ON HIV/AIDS AWARENESS (The Pretoria Student Law Review, 2021)
A gap exists in the South African media law with regards to HIV/Aids because HIV/Aids is normally dealt with in a scientific context rather than looking at the issue from a media law perspective. HIV/Aids is, however, still an issue which is highly relevant, particularly in a South African context, and oftentimes there is insufficient emphasis which is placed on the ever-growing pandemic in our country. Radio, television, newspaper and other forms of media possess the power to reach many people across the country and therefore they have an important and integral role to play in the fight against HIV/Aids. The media can have a significant impact on the stigmatisation of a person living with HIV/Aids and they will also have a role to play in the promotion of various preventative campaigns. The impact of the media on the disclosure of one’s HIV/Aids status should also be considered. Therefore, by conducting research and exploring these topics, it can be determined whether the media are fully utilising their power as an educational and preventative tool in the fight against HIV/Aids or whether there is room for improvement.
Keywords: HIV/Aids; South Africa; media law; stigmatisation